2020
DOI: 10.1093/biolre/ioaa125
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA-200 cluster on chromosome 23 is required for oocyte maturation and ovulation in zebrafish†

Abstract: The reproductive process is usually controlled by the hypothalamic-pituitary-gonad (HPG) axis in vertebrates, while Kiss/GnRH system in the hypothalamus is required for mammalian reproduction but dispensable for fish reproduction. The regulation of FSH/LH expression in fish species is still unknown. Here, we identified miR-200 s on chromosome 23 (chr23-miR-200 s) as important regulators for female zebrafish reproduction. Knockout of chr23-miR-200 s (chr23-miR-200 s-KO) resulted in dysregulated expression of lh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Therefore, CPE is still a good candidate for fish artificial propagation since it is rich in hormones and some factors, while the functions of some hormones have not been identified so far. Wnt4a and the miR-200 cluster on chromosome 23 are required for female reproductive duct formation in zebrafish and loss of each function led to defective reproductive duct development (Kossack et al, 2019;Xiong et al, 2020), which is similar to the phenotype of defective yellow catfish in current study. Interestingly, Oxytocin and Vasotocin are potentially responsible for zebrafish ovulation (Xiong et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, CPE is still a good candidate for fish artificial propagation since it is rich in hormones and some factors, while the functions of some hormones have not been identified so far. Wnt4a and the miR-200 cluster on chromosome 23 are required for female reproductive duct formation in zebrafish and loss of each function led to defective reproductive duct development (Kossack et al, 2019;Xiong et al, 2020), which is similar to the phenotype of defective yellow catfish in current study. Interestingly, Oxytocin and Vasotocin are potentially responsible for zebrafish ovulation (Xiong et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…Wnt4a and the miR-200 cluster on chromosome 23 are required for female reproductive duct formation in zebrafish and loss of each function led to defective reproductive duct development (Kossack et al, 2019;Xiong et al, 2020), which is similar to the phenotype of defective yellow catfish in current study. Interestingly, Oxytocin and Vasotocin are potentially responsible for zebrafish ovulation (Xiong et al, 2020). The genetic factors causing the defective reproductive duct in yellow catfish need further studies.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, both Avp and Oxt exposure upregulated a guppy oxtr paralogue, suggesting interaction between ovarian nonapeptide systems in the guppy ovary ( 82 ). In zebrafish, a recent study investigating downstream effectors linked to a reduced ovulation phenotype observed in female chromosome 23 miR-200 cluster KO mutants showed that co-injection of hCG, Avp and Oxt, but not injection of synthetic human GnRH and LH analogues were able to partially rescue the phenotype ( 159 ). Together, this data suggests a Gnrh-independent role for Avp and Oxt in zebrafish ovulation.…”
Section: Reproductive Function Of Nonapeptides In Teleost Fishesmentioning
confidence: 99%
“…The body weight of female zebrafish is heavier than that of males at adult stages, while loss of stat5b function not only reduces the sexual size dimorphism, but also attenuates the sex-biased gene expression in the liver (Huang et al, 2018;Xiong et al, 2017). The zebrafish microRNA-200 cluster on chromosome 23 (chr23-miR-200s) is predicted to target stat5b, and the females with deletion of chr23-miR-200s show significantly larger body sizes than wild type females at adult stages, whereas it has no obvious effect on the body size of male zebrafish (Xiong et al, 2018;Xiong et al, 2020a). Loss of dmrt1 function promotes the body growth of male zebrafish, but does not affect the growth of female zebrafish (Lin et al, 2017b).…”
Section: Genetic Basis Of Sexual Dimorphismmentioning
confidence: 99%